Assessment of pollution caused by tannery-waste and its impact on aquatic bacterial community in Hajaribag, Dhaka - Siddiqee, Mahbubul Hasan; Islam, Md Saiful; Rahman, M Majibur (Stamford Journal of Microbiology, 2013)
The leather industries of Hajaribag area, Dhaka city, produce hundreds of metric tons of inorganic and organic wastes which pollute the adjacent water bodies including the river Buriganga. In the present study, a total of 18 water samples from 6 different points along the effluent distribution route were examined. Along with the dissolved oxygen concentration (DO), acidity (pH), conductivity, and concentration of total dissolved solute (TDS), concentration of the samples were measured followed by the enumeration of total heterotrophic bacteria. Pure cultures of bacterial isolates were obtained after a brief enrichment and the isolates were biochemically identified up to genus level. The physicochemical test readings showed significant fluctuations in different points indicating radically heterogeneous conditions throughout the distribution system. The total count varied from 1.2x102 to 6.3x103 cfu/ml. Different bacterial genera including Alcaligenes spp., Bacillus spp., Corynebacterium spp., Escherichia spp., Micrococcus spp., Pseudomonas spp., Shigella spp., Staphylococcus spp. and Streptococcus spp. were isolated from the collected samples. The bacterial community was found to be diversified where the concentration of tannery waste was less; thereby it was assumed that the tannery waste might affect the aquatic bacterial community both quantitatively and qualitatively. DOI: http://dx.doi.org/10.3329/sjm.v2i1.15208 Stamford Journal of Microbiology, Vol.2(1) 2012: 20-23